Evaluation of double channel GMAW fillet welds of low carbon steel using solid wire - Mert, Tolga; Gultekin, Nurullah; Karaaslan, Ahmet (CARL HANSER VERLAG, 2015)
S235JR low carbon steel material with web and flange thicknesses of 8 mm was welded by conventional GMAW and double channel shielding gas method to form double fillet T-joints. The differences between these two methods were characterized by measurements of mean welding parameters, Vickers hardness profiles, molten and HAZ areas of the joints and thermal camera temperature measurements. According to the results, lower mean arc voltage along with lower heat input was obtained using double channel shielding gas method. Vickers hardness values were higher using conventional GMAW. Moreover, mean filler metal molten area values were higher using double channel shielding gas method, which depicted that this method increased productivity. Smaller HAZ area values acquired with double channel shielding gas method is an indication of more intense heat input.
Keywords: Double channel torch; low carbon steel; solid wire; T-joint; hardness; temperature measurement; molten and HAZ areas; GAS; Materials Science